Fishing effects on elasmobranchs from the Pacific Coast of Colombia - Andrés Felipe Navia; Paola Andrea Mejía-Falla (Universitas Scientiarum)
During 1995, 2001, 2003, 2004 and 2007; we studied the temporal variation in the structure of the elasmobranch assemblage along the Colombian Pacific coast using: the community index of diversity, heterogeneity, equitability, species composition, average catch sizes, and mean trophic levels. A total of 1711 specimens from 19 species (7 sharks and 12 rays) were collected during the 90 trawling operations. The number of species captured varied between 7 (1995) and 12 (2007) demonstrating a trend towards an imbalance in the assemblage attributes. In 1995, the mean trophic level (TLm) of the assemblage was 3.60, but in 2007 it decreased to 3.55 when the functional level of large predators was absent (TL ≥ 4). These results suggest changes in species composition, structural attributes, and a reduction of the highest functional level. Alterations to the catch proportions were also found: i.e. a greater abundance of rays of lower trophic levels. This study suggests an effect of trawling on the stability of this tropical coastal ecosystem.